Xotira haqidagi qarashlar va xotirani rivojlantirish - Rustamova Aziza Bekzod qizi, Tojiddin Yo’ldoshev Abdukarimovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In the article we will get acquainted with information about human memory, how it can be developed, with the definitions given by memory scientists, as well as the place of memory in life. To become a perfect person, a person needs religious and worldly knowledge, and to acquire that amount of knowledge, one must have a good memory.